Integrating Artificial Intelligence into Informatics Education: Effects on Students’ Analytical Reasoning and Creativity - Bayu Eka Ramadhan; Indra Maulana (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The integration of artificial intelligence (AI) in education is rapidly increasing; however, empirical evidence regarding its impact on students’ higher-order thinking skills in junior secondary informatics education remains limited, particularly within the Indonesian madrasah context. This study aims to examine the effect of AI integration in informatics learning on students’ analytical reasoning and creativity at MTs Negeri 9 Indramayu. A quantitative research design was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study involved 174 students who had experience using AI-based tools in informatics classes. Data were collected through a four-point Likert-scale questionnaire consisting of 14 items that met established validity and reliability criteria. The results show that AI integration has a positive and significant influence on both analytical reasoning and creativity, with a stronger effect observed on analytical reasoning. The structural model demonstrates moderate explanatory power and satisfactory predictive relevance. These findings contribute to educational technology research by providing empirical evidence that AI can function as a cognitive support system in informatics learning to foster higher-order thinking skills in the madrasah educational environment.